Risk-absorption: A Study on the power enhancer of cognition to reach a degree of interest in Investment through TISM approach. - Yadav Devi Prasad Behera, Dr. Saroj Kumar Sahoo, Tushar Ranjan Sahoo (International Journal of Advanced Science and Technology, 2020)
For the purpose of economic sustainability and self dependency in capital formation, retail investors are needed to be aware and understood, so that strategy can be formulated in enhance their risk absorption capacity and their interest for investment can be enhanced. In this regard the research question is “can the risk absorption enhance the strength of cognition to build expected degree of interest in investment?” The objectives of the study are to identify different dimensions of retail investors’ overall cognition, which affect their degree of interest in investment towards investment, and to justify the above said relationships through a model derived by using TISM. A term ‘risk-absorption’ used to enhance (mediator) the strength of cognition to build an expected degree of interest in investment. The study needed to focus the situational biases, acting as a moderator in the above said relationships. The study is descriptive in nature, where the relation is extracted logically by the help of TISM process and proposed a structural model. The word “risk absorption” is coined in this study, which reflects the character of an investor, who takes major investment risk and invest for a longer duration of time, repeated investment on the same financial product is expected, refer the financial product to other investor and wait for the falling investment to rise again, rather selling in the bearish phase. The study explained that the different dimensions of cognition in terms of types such as cold cognition, hot cognition, social cognition, and meta-cognition that affect the degree of interest in investors towards investment. Here the risk absorption can be inferred to play a mediating role in the effect of cognition on the interest of the investors and enhances the degree of interest in comparison to the direct effect of cognition on interest. The situational biases act as moderator during the direct effect as well the indirect effect as said above. This study can help the financial product makers and marketers to make mass communication strategies to encourage the retail investor and enhance their enthusiasm towards investment.